Measuring clinical performance using routinely collected clinical data. - Prytherch, D.R.
Following the well-publicized problems with paediatric cardiac surgery at the Bristol Royal Infirmary, there is wide public interest in measures of hospital performance. The Kennedy report on the BRI events suggested that such measures should be meaningful to the public, case-mix-adjusted, and based on data collected as part of routine clinical care. We have found that it is possible to predict in-hospital mortality (a measure readily understood by the public) using simple routine data-age, mode of admission, sex and routine blood test results. The clinical data items can be obtained at a single venesection, are commonly collected in the routine care of patients, are already stored on hospital core IT systems, and so place no extra burden on the clinical extra staff providing care. Such risk models could provide a metric for use in evidence-based clinical performance management. National application is logistically feasible.
Keywords: Clinical performance; Clinical data; Clinical outcome modelling; Hospital performance